(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cloud computing has revolutionized the way organizations store, manage, and process data. However, this paradigm shift has also brought about new challenges concerning data integrity and security. Ensuring the integrity of data stored in the cloud and implementing robust authentication mechanisms has become a critical concern. This survey paper provides a comprehensive overview of the diverse strategies and technologies available for safeguarding data integrity and authentication in cloud computing environments. We delve into the principles and practices behind data integrity, highlighting various authentication methods, cryptographic techniques, and access controls.